Determinants Analysis For The Quality Of Village Financial Statements - Chusnul Khotimah; Icuk Rangga Bawono; Rasyid Mei Mustafa (Universitas Muhammadiyah Malang, 2021)
This study aims to determine the effect of human resource competence, utilization of information technology, and public participation on the quality of village financial statement. This is a quantitative study which used a survey method and questionnaire. Furthermore, the samples were obtained using double sampling method with a total of 172 villages in Banyumas Regency. The collection of primary data was from respondents' answers to the questionnaire instrument that was distributed to the village secretary or treasurer as the PTPKD. The results showed that human resource competence did not affect the quality of village financial statement, while the utilization of information technology and public participation had positive effects. Furthermore, the study has three implications, first, the government is specifically expected to make good utilization of the provided information technology. Secondly , it is hoped that the central and regional governments can provide more intensive education and training to villages, in order to improve the competence of human resources, namely the village officials. Thirdly, the central and local governments as policymakers need to develop policies that villages universally can follow and do not overlap with one another.